2002
DOI: 10.1109/36.992827
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of nadir ocean surface emissivity on wind vector as measured with microwave radiometer

Abstract: Global brightness temperature observations of TOPEX/Poseidon microwave radiometer (TMR) at 18, 21, and 37 GHz have been collocated with near-simultaneous SeaWinds wind vector data as well as with monthly sea surface temperature and salinity products. The combined data allow us to study the dependence of zenith-directed ocean surface emissivity, at each frequency, upon both wind speed and direction. Results show a clear two-branch wind speed dependence; weak and linear below 7 m s with an increase in sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Combined with theoretical investigations [ 7 - 10 ], these results have suggested that nadir-looking radiometer directional sensitivity follows from the azimuthal anisotropy of the spatial curvature spectrum of short-gravity and capillary waves. Such expected signatures were further documented from TOPEX radiometer data [ 11 ]. Intuitively, from reciprocity between emissivity and reflectivity, such a directional sensitivity might also be expected on nadir radar cross section measurements.…”
Section: Introductionmentioning
confidence: 73%
“…Combined with theoretical investigations [ 7 - 10 ], these results have suggested that nadir-looking radiometer directional sensitivity follows from the azimuthal anisotropy of the spatial curvature spectrum of short-gravity and capillary waves. Such expected signatures were further documented from TOPEX radiometer data [ 11 ]. Intuitively, from reciprocity between emissivity and reflectivity, such a directional sensitivity might also be expected on nadir radar cross section measurements.…”
Section: Introductionmentioning
confidence: 73%
“…We again question what effect, if any, this variability might have on surface wind speed retrievals. Tran et al (2002) indicate that at 18 GHz and nadir incidence, the wind direction modulation of excess emissivity has a maximum magnitude of ϳ1.5 ϫ 10 Ϫ3 that occurs at around 11.5 m s Ϫ1 , with a leveling off or a slight decrease at higher wind speeds. Assuming a negligible frequency dependence, this corresponds to a ⌬T B of around 0.5 K, for which it should be noted is near the level of the SFMR's inherent instrument noise (see appendix B).…”
Section: Sensitivity To Surface Wind Directionmentioning
confidence: 94%
“…The profiles used to compute the transmission are labeled as follows: 1000-1004 mb and Ͻ995 mb storms are from data compiled by Sheets (1969); eyewall data from Frank (1977); eye data from Jordan (1957); Jordan mean tropical data from Jordan (1958) SFMR retrieval algorithm does not currently take this into account since the contribution of ocean surface roughness to the emissivity is assumed to be negligible at zero incidence. Previous studies (e.g., Tran et al 2002) have documented a modulation of the wind-induced excess emissivity by the orientation between satellite radiometers and the local surface wind vector (i.e., the angular difference between antenna polarization direction and sea surface roughness elements). At wind speeds above 10 m s Ϫ1 , as much as a 10% difference between cross-wind and up-/downwind induced excess emissivity has been observed.…”
Section: Sensitivity To Surface Wind Directionmentioning
confidence: 99%
“…The 18 and 37 GHz channels provided corrections for the effects of sea surface emissivity variations (due to surface winds) and cloud liquid, respectively. Because of the nadir viewing geometry, polarization effects were minimal, with a small effect due to wind direction dependency of the sea surface emissivity [ Tran et al , 2002]. All three TMR channels operated in a single linear polarization mode throughout the mission.…”
Section: Tmr Instrument Descriptionmentioning
confidence: 99%